Urban guidelines for public space planning in the city of Barquisimeto, Lara State (Gaceta Técnica, 2026)
This research aims to propose urban guidelines for the planning of public spaces in Barquisimeto, Lara State, Venezuela, aligned with global sustainable development trends. A mixed-methods approach was employed, integrating documentary and analytical research with field-based study. The process involved a multi-scale assessment of public spaces and current regulatory frameworks, benchmarked against successful international examples. The Central Macrosector was selected as the study area, identifying the Cultural Heritage Promenade" as a vital axis for the city. The proposal is grounded in four strategic pillars: sustainability, accessibility, sense of ownership, and comfort. The results provide an operational roadmap that goes beyond mere aesthetics, seeking to transform Barquisimeto into a benchmark for innovative and successful urban management regarding public space
Keywords: urban planning; Central Macrosector; PDUL